LEARNING TO WRITE POETRY TEXT BASED ON ACROSTIC MODEL WITH WORD CARDS THROUGH WORDWALL MEDIA - T. Muntazar; Asmaul Husna; Andriani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study discusses the effectiveness of learning to write poetry based on the acrostic model with word cards through Wordwall media. The acrostic model is used to help students compose poetry more systematically, while word cards function as a guide in selecting relevant vocabulary. The integration of Wordwall media aims to create more interactive and interesting learning. The method used in this study is a literature study that examines various sources related to learning to write poetry. The results of the study indicate that this approach is able to increase creativity, understanding of the concept of acrostic poetry, and students' motivation in writing. In addition, the use of Wordwall as an interactive learning medium allows students to more easily explore ideas and improve critical thinking skills in writing poetry. Therefore, this strategy is recommended as an innovative alternative in learning literature in schools.